Randomised clinical trial: dose optimising strategy by NUDT15 genotyping reduces leucopenia during thiopurine treatment of Crohn's disease. Issue 9 (25th September 2021) - Chao, Kang; Huang, Yibiao; Zhu, Xia; Tang, Jian; Wang, Xueding; Lin, Lang; Guo, Huili; Zhang, Caibin; Li, Miao; Yang, Qingfan; Huang, Jie; Ye, Lingna; et al.
Summary: Introduction: Thiopurine S‐methyltransferase (TPTM) is a well known biomarker for thiopurine‐induced leucopenia, which has limited value in Asia. Instead, NUDT15 C415T is a promising predictor in Asia. Aims: To explore whether an optimised strategy based on NUDT15 C415T genotypes affects thiopurine‐induced leucopenia, as well as efficacy in Chinese patients with Crohn's disease. Methods: Patients with Crohn's disease and indications for thiopurines were included from two hospitals in China. They were randomly assigned to either the intervention or the control group. In the intervention group, those with genotype CC received a standard dose (control group), those with CT genotype received 50% of the standard dose, those with TT genotype received alternative drugs. The primary endpoint was thiopurine‐induced leucopenia (<3.5 × 10 9 /L). Secondary outcomes were the incidence of other adverse events and the efficacy for maintaining steroid‐free remission at week 36. Results: The rate of thiopurine‐induced leucopenia was lower in the intervention group (n = 52) than in the control group (n = 66) (23.7% vs 32.4%, P = 0.049, RR = 0.73, 95% CI 0.53‐1.00). In CT subgroup, the incidence of leucopenia in the intervention group (n = 10) was significantly lower than in the control group (n = 28) (31.3% vs 65.1%, RR = 0.48, 95% CI 0.28‐0.84). Neither other adverse events nor treatment efficacy was significantly different between the two groups during follow‐up. Conclusions: Among Chinese patients with Crohn's disease, dose optimisation by NUDT15 C415T reduced the rate of thiopurine‐induced leucopenia, without significant influence on efficacy. Using 50% dose reduction for heterozygotes, and alternative drugs for homozygotes, are practicable strategies. Clinical trial number: NCT02929706. Abstract : Accounting for land use and climate changes in a combined way based on extensive data allowed us to identify urbanization as the major driver of phytoplankton development in lakes located in urban areas, and climate as major driver in lakes located in remote areas where past and future land use changes were minimal. The results of this large scale study suggest the best approaches for mitigating the effects of human activity on lake phytoplankton and cyanobacteria will depend strongly on lake sensitivity to long‐term change and the magnitude of projected land use and climate changes at a given location.